Children From Multilingual Families: A Global Perspective With Insights From Uzbekistan. (Zien Journal of Social Sciences and Humanities, 2025)
As globalization accelerates, an increasing number of children grow up in multilingual environments, acquiring two or more languages simultaneously. While multilingualism enhances cognitive flexibility and adaptability, it may also pose challenges for speech development. Some multilingual children experience articulation difficulties, expressive language delays, or phonetic interference, raising concerns about the impact of early exposure to multiple languages on speech acquisition. This study examines the most common speech disorders in multilingual children based on the ICD-10 (International classification of diseases-10 Publication 2023 ) and explores findings from longitudinal studies conducted in Canada, the U.S., Singapore, Switzerland, and Uzbekistan. Additionally, it evaluates global intervention strategies used to support speech development in multilingual children. The research highlights the need for multilingualspecific speech assessments, particularly in Uzbekistan, where early English and Russian language instruction is growing. Findings suggest that while multilingual children may experience temporary speech delays, these are often due to language interference rather than developmental disorders. The study emphasizes the importance of tailored speech therapy approaches to prevent misdiagnosis and ensure optimal language development.